1999
DOI: 10.1021/la9900932
|View full text |Cite
|
Sign up to set email alerts
|

An AFM Study of Lipid Monolayers. 2. Effect of Cholesterol on Fatty Acids

Abstract: In this study the effect of cholesterol in Langmuir-Blodgett monolayers of fatty acids of varying chain lengths was investigated by atomic force microscopy (AFM). Domain formation due to lateral phase separation was studied at different lipid compositions and surface pressures. A small amount of cholesterol is miscible with palmitic acid (C16:0) and forms a flat monolayer while excess cholesterol forms a rougher cholesterolrich phase. No miscibility was observed in monolayers of lignoceric acid (C24:0) and cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 28 publications
(58 reference statements)
3
67
0
1
Order By: Relevance
“…The deposited lipid Wlm was left for 25 min for the solvent to evaporate, and thereafter compressed to 22 mN/m at a speed of 1 mN/m per minute, with a maximum barrier speed of 10 mm/min (cf. Ekelund et al, 1999;Sparr et al, 1999). Three isotherm cycles were performed to ensure reproducibility.…”
Section: Preparation Of Langmuir-blodgett Lipid Monolayer Wlmsmentioning
confidence: 99%
“…The deposited lipid Wlm was left for 25 min for the solvent to evaporate, and thereafter compressed to 22 mN/m at a speed of 1 mN/m per minute, with a maximum barrier speed of 10 mm/min (cf. Ekelund et al, 1999;Sparr et al, 1999). Three isotherm cycles were performed to ensure reproducibility.…”
Section: Preparation Of Langmuir-blodgett Lipid Monolayer Wlmsmentioning
confidence: 99%
“…In order to study the capability of penetration of synthetic molecules into cell membranes, simplified models are often employed. Typical examples in this context are Langmuir monolayers of phospholipids at the air-water interface, which represent a half leaflet analogue of biological membranes [6][7][8][9]. Due to the simple preparation and characterization of Langmuir films, they are used to study the interactions between membrane components [10], protein interactions with the lipid matrix [11], and the penetrability for synthetic molecules [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Another essential component in biological membranes is cholesterol, which is responsible for stabilization and fluidization of the membranes [7,[24][25][26][27][28]. Numerous publications investigate the interaction of cholesterol and phospholipids in mixed Langmuir and LB films [29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Phase separation may also occur in the presence of cholesterol. 17 It has been shown that lateral phase separation of cholesterol leads to deformed non-spherical vesicles. 18 Facetted vesicular structures have been observed by Mel 'nikova et al 19 in mixed systems of dioctadecyldimethylammonium bromide (DODAB) and dioleoyl phosphatidylethanolamine (DOPE) (4:1).…”
mentioning
confidence: 99%